المذهب الأدبي الإسلامي والمذاهب الغربية من النقد إلى البديل - العيد, حنكة; أحمد, خضرة (جامعة الوادي - University of Eloued, 2021)
بدأت حركة الأدب الإسلامي ونقده مع بداية حركة النهضة الفكرية الإسلامية الجديدة , وأخذت الفكرة الأدبية والنقدية المنبثقة عن التصور الإسلامي للكون والحياة والإنسان تنمو شيئا فشيئا وتتبلور نتيجة الأوضاع التي يشهدها العالم العربي والإسلامي, بل واقتضى الأمر أن تتميز الرؤية الإسلامية كمذهب مستقل في الأدب والنقد لتقف في وجه المذاهب الغربية الجديدة التي تتميّز بمرجعية فلسفية خاصة بها تنبع من فكرها وأيديولوجيتها, ومنه بدت الحاجة ملحّة إلى الكشف عن معالم نظرية النقد الإسلامي المنبثقة عن الرؤية الإسلامية للإنسان والحياة والكون والتي جاءت لتخلص الأدب من سطوة مذاهب الأدبي الغربية غير المتوافقة مع تصورات ومعتقدات الدين الإسلامي, والكشف عن المذهب الإسلامي البديل ورواده , وأهمّ مسوغاته .. الكلمات المفتاحية : المذهب ؛ الإسلامي ؛ الرؤية ؛ الغربي ؛ البديل؛ النقد. Abstract: The Islamic literary movement and its criticism began with the beginning of the new Islamic intellectual renaissance movement. The literary and monetary idea emanating from the Islamic conception of the universe, life and human being gradually grew and crystallized as a result of the situation in the Arab and Islamic world. The face of the new Western doctrines characterized by philosophical reference And from it emerged the urgent need to reveal the features of the theory of Islamic criticism emanating from the Islamic vision of man and life and the universe, which came to get rid of the literature of the Western literary doctrines incompatible with the perceptions and beliefs of the Islamic religion, and the disclosure of alternative Islamic doctrine and pioneers, and the most important His reasons . key words: ؛ Islamic؛ - vision ؛Western ؛ alternative ؛-doctrine criticism.
مقال
Keywords: المذهب ؛ الإسلامي ؛ الرؤية ؛ الغربي ؛ البديل؛ النقد; Islamic؛ - vision ؛Western ؛ alternative ؛-doctrine criticism.